Influence of Tönnis Grade on Outcomes of Arthroscopy for FAI in Athletes: A Comparative Analysis - Byrd, J. W. Thomas (Orthop J Sports Med, 2017)
OBJECTIVES: Clear radiographic features indicating poor results of arthroscopy in the surgical correction of femoroacetabular impingement (FAI) include less than 2mm of joint space and Tönnis 3 changes. Favorable results may be associated with Tönnis 0 and 1, but Tönnis 2 findings are associated with a broad spectrum of joint damage. The purpose of this study is to define the outcomes based on Tönnis findings among a previously reported cohort; including a comparative analysis of Tönnis grades O and 1 versus Tönnis grade 2 changes. METHODS: These authors previously published their initial experience in the first 200 consecutive athletes undergoing arthroscopic correction of FAI with minimum 1 year F/U. For this current study, these previously reported outcomes were correlated with the Tönnis grade, using the Tönnis system commonly adopted by third-party insurance carriers. The Tönnis grade was determined independently by two experienced clinicians. These were subsequently compared, and in cases where an agreement was not reached, the lower of the two grades was used so that the Tönnis grade was not being overestimated. The influence of Tönnis on patient reported outcome scores (modified Harris Hip Score) and return to sport was assessed. Independent variables of gender as a categorical variable and age as both a continuous and categorical (those above and below the median age) variable were evaluated. RESULTS: The average age of this previously reported cohort was 28.6 years (range11-60), with 148 males and 52 females. There were 40 Tönnis 0 (average age 29; 28 males & 12 females), 112 Tönnis 1 (average age 30; 88 males & 24 females), 45 Tönnis 2 (average age 27; 30 males & 15 females), and 2 Tönnis 3 (average age 33; 1 male & 1 female). The Tönnis 3 data was too small for statistical analysis, as only 2 patients with severe femoral deformities were included. The average improvement was Tönnis 0 23.1 points (preop 69.0; postop 92.1), Tönnis 1 20.6 points (preop 73.9; postop 94.5), Tönnis 2 16.4 points (preop 71.6; postop 88.0), and Tönnis 3 23.5 points (preop 61.5; postop 85). As would be expected, there was a trend (p=0.055) towards lower scores with increasing Tönnis grade, but this was not statistically significant. There was both statistically (p<0.01) and clinically (>5pts) significant improvement across all Tönnis grades; and there was no statistically significant difference between Tönnis 0 and 1 compared to Tönnis 2 (p=0.078). The percent that returned to sport was: Tönnis 0 95%, Tönnis 1 92%, Tönnis 2 85%, and Tönnis 3 100%. Similar to outcome scores, there was a trend (p=0.098) towards lower rates of return to sport with increasing Tönnis grade, but it was not statistically significant; and there was no statistically significant difference between Tönnis 0 and 1 compared to Tönnis 2. Within each grade, there was no correlation with age, such that increasing age did not reflect lower scores. There was also no correlation with gender. CONCLUSION: Tönnis grade is an objective radiographic parameter used in staging the severity of degenerative disease. It is likely that these radiographic features provide a limited representation of the extent of joint damage. It is equally likely that successful outcomes of arthroscopic intervention may be as much dependent on subjective parameters such as patient expectations and desires. This data supports that successful outcomes can be encountered even among those with Tönnis 2 radiographic features, comparable to those with Tönnis 0 and 1 changes.